Reproduksi Sehat, Remaja Sehat di Posyandu Remaja Pashmina - Miftachul Jannah; Pedvin Ratna Meikawati; Swasti Artanti (LPPM Akbid Harapan Ibu Pekalongan, 2021)
Adolescents are people aged 12 to 24 years. Adolescence is a transition from childhood to adulthood. This means that the process of introduction and knowledge of reproductive health has actually started at this time. In simple terms, reproduction comes from the word